THE FISHERIES SUBSIDIES IN INDONESIA AND CHINA - Wicaksono, Bayu Rhamadani (Jurnal Ekonomi & Studi Pembangunan, 2019)
The World Trade Organization (WTO) considers sustainable economic development. One of the regulations arranged is the unfair trade that several activities will be eliminated in the future, including the fisheries subsidies. The objectives of this research are (1) understanding the general descriptions about fisheries subsidies in Indonesia and China; (2) how large the impacts of fisheries subsidies that are linked with the policies; and (3) the opinion whether the fisheries subsidies must be stopped or not. This research use the literature studies from several sources and the supplementary data are also included to strengthen this study. Based on the result and discussion, the fuel subsidies are the largest fisheries subsidies in both Indonesia and China. Although the fuel subsidies are harmful and burden the government budget, the policy of subsidies is still needed, especially in the developing countries, including Indonesia. Those subsidies contribute the positive effects to the fisheries sector performance. On the other hand, eliminating fisheries subsidies, particularly the fuel subsidies, is expected to provide the negative impacts. For the policy, the government regulates the programs in the fisheries sector. There are two feasible schemes in the fisheries market in case talking about the fisheries subsidies with the aim of a trade policy tool and sustainability. The author does not agree if the fisheries subsidies stopped. The government must evaluate the subsidy policies that can be connected with the fisheries sector performance indicators and must still prepare state budget for fisheries subsidies, especially subsidies for small-scale household, such as fishers. The fisheries subsidies should be continued with applied terms and conditions, so the subsidies will be used wisely by the fisheries business actors and will be appropriately monitored by the government